Swear Words Used In The Movie “Fast And Furious 6” - Ulan Sari, Ni Made (Humanis; Vol 22 No 1 (2018), 2018)
Language is used as a means of communication in social intercourse. It can be used to propose one’s ideas, deliver particular messages, and to express emotions. One of many ways of using language is by producing swear word. Swear word is an offensive word which often used to express humiliation, anger and any other tense emotions. This study concerns with the descriptive analysis of swear word found in Fast and Furious 6 movie and its function. Hopefully, this study will be useful for English Department students and also the viewers of the movie to gain better understanding in interpreting the meaning and function of the swear word found in the movie.The research method employed in this study is descriptive qualitative method. The data were collected through observation and documentation method. The data was taken from the dialogue among the characters in the movie and its subtitles. Then, the deductive-inductive method was used in the step of the data analysis. Furthermore, in presenting the analysis, the data is explained descriptively in words, supported by tables.The finding presented that there are six kinds of swear words proposed by Hughes (2006) are performed by the characters in Fast and Furious 6 movie. There are seven swear words that related to sex (ass, asshole, ass-kicking, pussy, big-ass, bad-ass), two swear words related to excrement (shit and bullshit), a swear words related animal’s name (fox), three swear word related to personal background (bitch, son of a bitch, bastard), a word related to sexual activity (fuck) and three words related to taboo or religion or oath (hell, damn, goddamn). Meanwhile, swear word related to mentall illness and racism was not found in the movie. Furthermore, the function of swear words performed by the character of the movie are used as abusive swearing, cathartic swearing, idiomatic swearing and emphatic swearing. Swear word which used as dysphemistic swearing is not found in the movie.